2020
DOI: 10.1080/17597269.2020.1835452
|View full text |Cite
|
Sign up to set email alerts
|

Biogas potential determination and production optimisation through optimal substrate ratio feeding in co-digestion of water hyacinth, municipal solid waste and cow dung

Abstract: Modelling and optimisation of biogas production from different substrate mixtures is lagging behind in research and development. Current biogas production processes are not fully exploiting co-digestion of multifaceted biomaterials with manures and other biowastes. A model is presented for the determination of biogas production potential from Water Hyacinth (WH), Municipal Solid Waste (MSW), and Cow Dung (CD) as well as the subsequent optimisation of the co-digestion mix ratios of these substrates. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 59 publications
2
16
1
Order By: Relevance
“…This value agrees with the ranges reported in the former review [24]. Using different feedstocks in anaerobic digestion, depending on their C/N ratios, improves anaerobic digestion performance and signi cantly increases biogas generation and biodegradability [53]. Furthermore, biogas production was reduced at the highest/lowest percentage of the C/N ratio due to a higher/lower nitrogen consumption rate from acid-producing microbes than from methanogenic microorganisms [20].…”
Section: Impact Of Fw Addition On Ch and Wh For Biogas Productionsupporting
confidence: 89%
See 1 more Smart Citation
“…This value agrees with the ranges reported in the former review [24]. Using different feedstocks in anaerobic digestion, depending on their C/N ratios, improves anaerobic digestion performance and signi cantly increases biogas generation and biodegradability [53]. Furthermore, biogas production was reduced at the highest/lowest percentage of the C/N ratio due to a higher/lower nitrogen consumption rate from acid-producing microbes than from methanogenic microorganisms [20].…”
Section: Impact Of Fw Addition On Ch and Wh For Biogas Productionsupporting
confidence: 89%
“…In this study, the maximum CBY recovered at the optimum C/N ratio was improved by 179.7 and 51.36% when compared with the C/N ratios of 34.46 (mono digestion of CH) and 25.53 (mono digestion of WH), respectively. This improvement is comparable with the study of Kunatsa et al [53], who achieved the best improvement of biogas yield by 157.11% at WH, municipal solid waste (MSW), and cow manure (CM) mixture of (53.27:24.64:22.09) over water hyacinth alone.…”
Section: Impact Of Fw Addition On Ch and Wh For Biogas Productionsupporting
confidence: 86%
“…This fluctuation is owing to the excess formation of volatile fatty acids (VFAs) [19,75]. In the past, in AD, different wastes, such as municipal solid waste, food waste, kitchen waste, and animal manure, were used for biogas generation [50,[76][77][78]. However, recently, attention has shifted to the co-digestion of lignocellulose material with kitchen waste, food waste, and animal manure to generate biogas due to various advantages [14,47,79].…”
Section: Biogas Yieldmentioning
confidence: 99%
“…Co-digestion has the potential to increase methane yield and reduce the duration of incubation ( Unpaprom et al, 2020 ). Some studies indicated that the use of food waste, cow dung and some other organic waste decreased the incubation to 30 days ( Priya et al, 2018 ; Kunatsa et al, 2020 ). In some cases, microbial pretreatment was used to generate methane from WH.…”
Section: Advanced Bioprocesses For Water Hyacinth Valorizationmentioning
confidence: 99%